Application of biochar for enhancing cadmium and zinc phytostabilization in vigna radiata L. cultivation - Prapagdee, Songkrit; Piyatiratitivorakul, Somkiat; Petsom, Amorn; Tawinteung, Nukoon (My University, 2014)
Cadmium (Cd) is a toxic and nonessential element. Because of its toxicity, Cd soil contamination is a major environmental risk to living organisms. Several studies have reported on the successful use of biochar to immobilize Cd in soil as it reduces Cd accumulation in plant parts. This research reports on the contrasting effect of biochar on enhancing Cd uptake by plants. A cassava stem biochar produced through low-temperature pyrolysis was applied to natural Cd-contaminated soil that also had a high zinc (Zn) concentration. Vigna radiata L. (a green bean) was grown in treatments receiving three biochar rates, i.e., 5, 10, and 15 %, respectively. The results showed that the 10 % biochar-amended soil had a positive effect on promoting plant growth and seed yield. Unfortunately, 15 % biochar-amended soil caused an adverse effect to plant growth. Cadmium uptake by plants increased with increasing biochar application rate. Zinc uptake by plants tended to decrease with biochar application. Cadmium and Zn bioavailability in soil was significantly reduced with an increasing biochar application rate. The results also showed that the biochar-amended soil could be an alternative and cost-effective method to promote plant growth and decrease Cd mobility in soil. The ratio of Cd concentration in plant root to soil was higher than 1, while the translocation factor from root to shoot was less than 1. These results indicate that the cultivation of V. radiata L. coupled with biochar application is an appropriate method to enhance Cd phytostabilization efficiency of V. radiata L. in Cd-polluted sites.
Keywords: Bioavailability; Cadmium; Cassava stem biochar; Phytostabilization; Vigna radiata L.; Zinc